Digital entrepreneurship as a result of the transformation of the labor market in a pandemic - Suieubayeva, S.N.; Nurekenova, E.S.; Rakhimberdinova, M.U.; Granetskiy, V.N. (BUKETOV BUSINESS REVIEW, 2023)
Object: Study the impact and adaptation of digital information system of the economy on the development of the level of small and medium-sized enterprises, increasing the labor market in pandemic conditions. Study of how the economy’s digital information system has affected and evolved small and medium-sized business development, as well as the growth of the labor market in conjunction with the pandemic. Methods: The theoretical literature on this topic served as the foundation for the study’s methodology. Emerging problems of the labor market of Kazakhstan in the conditions of COVID-19 pandemic were identified through qualitative and quantitative analysis of statistical data. The analytical part of the study organizes the findings from the examination of the Republic’s small- and medium-sized business support programs, which allowed for the evaluation of economic processes overall and the formulation of broad conclusions. Findings: The study identifies relevant aspects of the development of digital entrepreneurship in the modern economy; the scientific approach to the concept of digital economy and digital entrepreneurship is implemented as a result of the study of literary sources; the factors that have a significant impact on the transformation of the functioning labor market are identified; the degree of influence of these factors on the Kazakh economy is determined. For a qualitative change in the labor market, the authors identified a tangible need to increase the digital literacy of the population, new thinking skills, increase the level and quality of education, which will undoubtedly change the structure of human resource potential and ultimately increase labor productivity. Entrepreneurs have unique opportunities to apply high-tech inventions in practice to improve the business model of organizations. Thus, the following opportunities open up: the emergence of digital platforms as representatives of fundamentally new institutions; the emergence of the “peer-to-peer” communications function, when opportunities arise for communication participants directly without a company and market; the emergence of effective organizations with a reduced middle management function and increased directive control. Conclusions: This study analyzes digital mechanisms that search for new opportunities for employment in Kazakhstan’s economy. In today’s economy, a necessary requirement for its successful development is undoubtedly the development of a digital environment. To characterize the ways of introducing digital tools into business processes, the state Program “Digital Kazakhstan”, aimed at supporting economic entities, was studied. The study analyzed the employment of people in digital business. An assessment was also made of the degree of transformation of Kazakhstan’s employment models depending on arising emergency situations. An important aspect of the work is the development of recommendations for the further expansion of business digitalization.